Bibliografia przekładów na język śląski w latach 2002—2018 / Bibliography of translations into the Silesian language in the years 2002—2018 - Pospiszil, Karolina (Przekłady Literatur Słowiańskich, 2019)
The bibliography includes translations into the Silesian language made both in the standard script as well as in the non-standard one. The starting point for translations into the contemporary Silesian may be dated back to 2002. Since then, there have been irregularly published, usually in the form of collections, translations of various literary genres (with a preponderance of poetic forms) from dozen or so world languages, such as: Greek, Latin, French, German, Polish, Mandarin Chinese, English, Welsh, Russian, or the Upper Sorbian. No single translation from Silesian into other language is included, since heretofore no such a translation has been made.